2018
DOI: 10.24036/jmpe.v1i2.4762
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Motivasi Memasuki Dunia Kerja Dan Prestasi Belajar Terhadap Kesiapan Kerja Mahasiswa Jurusan Pendidikan Ekonomi Fakultas Ekonomi Universitas Negeri Padang

Abstract: This study aimed to examine the effect of motivation to enter the workforce and workplace readiness achievement of learning on students majoring in economics education field state university economic faculties. This research is causative. The population in this study were all students majoring in economics education UNP force in 2014 by using primary data and secondary data. The analytical method used is multiple regression analysis using SPSS version 17. The results of this study indicate that 1) the motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
4
0
5
Order By: Relevance
“…The motivation built for accounting students of vocational high schools encourages students to continue their studies to increase work readiness in the accounting profession. Motivation to be ready to work is created in the final semester students of the Department of Economic Education (Junaidi, Armida, & Susant, 2018). Dirwanto, 2008 in (Junaidi et al, 2018) states that job readiness is formed not only with motivation and learning achievement but through experience, skills, personal appearance, attitudes, interests and family economic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation built for accounting students of vocational high schools encourages students to continue their studies to increase work readiness in the accounting profession. Motivation to be ready to work is created in the final semester students of the Department of Economic Education (Junaidi, Armida, & Susant, 2018). Dirwanto, 2008 in (Junaidi et al, 2018) states that job readiness is formed not only with motivation and learning achievement but through experience, skills, personal appearance, attitudes, interests and family economic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Motivation to be ready to work is created in the final semester students of the Department of Economic Education (Junaidi, Armida, & Susant, 2018). Dirwanto, 2008 in (Junaidi et al, 2018) states that job readiness is formed not only with motivation and learning achievement but through experience, skills, personal appearance, attitudes, interests and family economic conditions. H2 data analysis showed that interest can affect job readiness of accounting students majoring in accounting in the accounting profession.…”
Section: Discussionmentioning
confidence: 99%
“…Tidak saja program ini mempunyai tujuan membangkitkan motivasi santri untuk bekerja dengan penuh motivasi dan juga dikuasainya pengetahuan soft skill dasar dalam berkomunikasi dan memecahkan masalah. Hal ini karena pemberian materi motivasi memungkinkan peserta bisa melihat perspektif dunia kerja dengan benar dan meningkatkan kinerja mereka nantinya (Samiono, 2021) (Ayuningtyas, 2015) dan (Nia Junaidi, 2018). Namun juga diakhir program peserta mempunyai kepuasan atas pelaksanaan program peningkatan soft skill pengembangan diri ini.…”
Section: Pendahuluanunclassified
“…Dalam penelitian Yuniasari dan Djazari (2017) membahas "Pengaruh Minat Menjadi = Guru, Lingkungan Keluarga, dan Pengenalan Lapangan Persekolahan (PLP) Terhadap Kesiapan Menjadi Guru", juga hanya meneliti dua variabel bebas. sedangkan pada penelitian Junaidi et al (2018) meneliti "Pengaruh Lingkungan Keluarga, Prestasi Belajar, dan Motivasi Mahasiswa terhadap Kesiapan Menjadi Guru" yang hanya membahas prestasi belajar yang mana hasil penelitiannya menemukan bahwa prestasi belajar sangat memuaskan dalam kesiapan menjadi guru.…”
Section: Pendahuluanunclassified